INTRODUCTION OF A WORKFLOW FOR TOMOGRAPHIC ANALYSIS OF FORMATION STIMULATION USING NOVEL NANO-BASED ENCAPSULATED ACID SYSTEMS - Petrakov, Dmitri; Jafarpour, Hamed; Qajar, Jafar; Aghaei, Hamed; Hajiabadi, Hasan (Journal of Applied Engineering Science, 2020)
During the production time, it is crucial to manage the reservoir efficient productivity and keep it at a profitable level. Matrix acidizing in carbonate reservoirs is a common course of action to increase the efficiency of production. The present project is based on an integrated multi-disciplinary plan as an arena to merge traditional and novel technologies in the field of petroleum engineering, petroleum geoscience, chemical engineering, computer vision and mineralogy. Some crucial parameters such as permeability/porosity changes occurred during carbonate acidizing are modelled and analyzed based on various modern technologies, such as, the novel digital rock technologies. A waste variety of nanoparticles is also used in order to design a novel acid mixture for stimulating the carbonate reservoirs. Specifically, this study is considered as a one-step forward in development of smart encapsulated acid systems using a range of hydrophobic silica nanoparticles in various grades of hydrophobicity. Moreover, the present study can be considered as the first practical example for application of digital rock physics in improvement of acidizing operation in Iran and Russia. The proposed research methods are consist of preparation of encapsulated acids, sample and data collection, conventional core analysis, digital core analysis, lab experiments and modelling and conclusion. Characterization of the efficiency of this process was once more characterized using the aforementioned digital rock technologies to visualize the effect of encapsulated acid fracturing operation, impact of surface modification of silica NPs on the etching efficiency, the physical properties of core samples, and subsequently the final productivity index. Thin section, SEM and FE-SEM analysis was then performed to further evidence the efficiency of this method. Moreover, the efficiency of this method was categorized based on the identified mineralogy and rock composition. It was concluded that the dissolution rate was significantly increased as a result of acid neutralization control and the reaction rate decreased which in turn resulted inmore homogenous patterns of wormholes, higher permeability, and so, more successful acid treatment. Thanks to the reduced accessible surface of acid systems caused by their emulsion-based nature, it was found that this novel encapsulation process can reduce the risks of corrosion in all the equipment in surface and bottom hole. It naturally reduces the extra costs of corrosion-related damages and subsequent workover operations, which are the common need of most of the wells treated by conventional acid fracturing operations.